SPATIAL MODELING IN SUSTAINABLE PEAT LAND MANAGEMENT BASED ON PEAT HYDROLOGICAL UNITS (KHG) - Turmudi, Turmudi; Suwarno, Yatin; Munajati, Sri Lestari; Suryanta, Jaka (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2021)
Utilization of peatlands becoming more massive from time to time. On the other hand, efforts are needed to ensure the sustainability of peatland functions for the environment. In an effort to support the sustainability of peatland functions, spatial modelling with the basis of KHG is needed to facilitate its management. This study aims to provide input on the optimization of peatlands based on KHG to be used for the community, while maintaining its sustainability. The method used is spatial analysis that covered data KHG, Land Unit, Soil, Ground water level (GWL), Rainfall data. The results of the study show that KHG helps to more focus on determining the AOI (Area of interest) to be researched. The inputs needed for research based on KHG, are:- KHG analysis of: 1. land unit; 2. Rainfall data, 3. GWL data, 4. Soil data. that can identify KHG areas that need attention to be managed properly:the tidal peatland, and the peat dome for conservation efforts. Analysis of KHG with rainfall and GWL, it can be obtained the months (February and November) which function as controls on the success of management through the GWL value.